RETRACTION NOTICE: Research into the process of carbonate conversion of phosphogypsum in the water media (Technology audit and production reserves, 2025)
RETRACTION: Yelatonsev, D. (2021). Research into the process of carbonate conversion of phosphogypsum in the water media. Technology Audit and Production Reserves, 3(3(59)), 10–13. https://doi.org/10.15587/2706-5448.2021.235243 The above article, published online on June 30, 2021 in the Archive of the "Technology Audit and Production Reserves" journal https://journals.uran.ua/tarp/issue/archive, has been retracted in accordance with the editorial policy on retractions and corrections of published articles https://journals.uran.ua/tarp/rules. The retraction of the article was initiated by the author. The results of the editorial board's internal investigation confirmed a violation of publication ethics: Fig. 1, Fig. 2, the numerical data for Tables 2, 3 and 4 were borrowed from Ndjimbi, L. U. O. (2014). Production of Calcium Carbonate From Phosphogypsum Wastes. Master’s Dissertation, University of Pretoria. Available at: https://repository.up.ac.za/items/ff29c274-d952-4dc0-93f2-87d6808f8a8d without proper citation. This was the basis for the retraction of the article.